1998
DOI: 10.1074/jbc.273.43.27786
|View full text |Cite
|
Sign up to set email alerts
|

An Eukaryotic RuvB-like Protein (RUVBL1) Essential for Growth

Abstract: A human protein (RUVBL1), consisting of 456 amino acids (50 kDa) and highly homologous to RuvB, was identified by using the 14-kDa subunit of replication protein A (hsRPA3) as bait in a yeast two-hybrid system. RuvB is a bacterial protein involved in genetic recombination that bears structural similarity to subunits of the RF-C clamp loader family of proteins. Fluorescence in situ hybridization analysis demonstrated that the RUVBL1 gene is located at 3q21, a region with frequent rearrangements in different typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
145
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(156 citation statements)
references
References 41 publications
9
145
1
1
Order By: Relevance
“…These multiple interactions of Pontin/Reptin suggest an essential physiological role, and studies in S. Cerevisiae have demonstrated that yeast orthologs of both Reptin and Pontin are required for cell viability without overall shutdown of transcription. 7,8 Essential deveopmental roles in Drosophila and Xenopus have also been observed. 9,10 However, the only information currently available about their role in mammalian cells is that knockdown of Pontin in human diploid fibroblasts causes proliferation arrest, 11 and that knockdown of Ruvbl1 (and other Tip60 complex components) in embryonic stem (ES) cells induces loss of pluripotency.…”
Section: Introductionmentioning
confidence: 92%
“…These multiple interactions of Pontin/Reptin suggest an essential physiological role, and studies in S. Cerevisiae have demonstrated that yeast orthologs of both Reptin and Pontin are required for cell viability without overall shutdown of transcription. 7,8 Essential deveopmental roles in Drosophila and Xenopus have also been observed. 9,10 However, the only information currently available about their role in mammalian cells is that knockdown of Pontin in human diploid fibroblasts causes proliferation arrest, 11 and that knockdown of Ruvbl1 (and other Tip60 complex components) in embryonic stem (ES) cells induces loss of pluripotency.…”
Section: Introductionmentioning
confidence: 92%
“…The R2TP module RUVBL1 and RUVBL2 (RVB1 and RVB2; TIP49 and TIP48; pontin and reptin) RUVBL1 and RUVBL2 are ATPases of the AAA+ superfamily (ATPase associated with diverse cellular activities) and are related to the prokaryotic DNA helicase RuvB (Qiu et al 1998;Kanemaki et al 1999), which is involved in homologous recombination and doublestrand break repair (see Fig. 2 for a schematic representation of the R2TP module components).…”
Section: Introductionmentioning
confidence: 99%
“…Because TIH1 had been shown to be an essential gene (9,19,22), we first asked if TIH2 is also required for viability. The TIH2 gene was disrupted as described under "Experimental Procedures."…”
Section: Tih2mentioning
confidence: 99%
“…The recombinant TIP49a is an ATP-dependent DNA helicase (18). Meanwhile, a human homologue of p50, RUVBL1, was shown to co-purify with RNAP II holoenzyme, and the yeast counterpart was reported to be essential for viability (19). Furthermore, in a search for proteins that interact with ␤-catenin, two novel human proteins, 52-and 44-kDa, were detected (20).…”
mentioning
confidence: 99%